Olive oil: adulteration from 1993 to 2000 - Aued-Pimentel, Sabria (2002)
In the period of January 1993 to September 2000 were analyzed at Adolfo Lutz Institute 236 samples of olive oils and in all of the samples the purity was verified through the analysis of the fatty acids profile, using gas chromatographic techniques. In 136 samples it was also verified if the classification on the label was in accordance with the quality. The absorption measures in the ultraviolet spectra, at 232 and 270 nm were the parameters evaluated. It was observed that 43 samples (18,2%) were adulterated and the main fraud type was the addition of vegetable oils of lower commercial value, mainly soybean oil. Considering the label evaluation, 7 samples (5,1%), of the 136 analyzed, presented incorrect qualityclassification. It was verified that from the total samples, 77 were picked by the Sanitary Survey Watch and, of these, 67 were picked from 1997 to 2000, due the cooperation programs established from 1997 between the Adolfo Lutz Institute and the Center of Sanitary Survey Watch of the State of São Paulo.